Relationships between plasma levels and six proinflammatory interleukins and body composition using a new magnetic resonance imaging voxel-based technique. Issue 1 (March 2021) - Strand, Robin; Kullberg, Joel; Ahlström, Håkan; Lind, Lars
Graphical abstract: Highlights: IL-1RA and IL-6 levels were related to traditional DXA and MRI measurements of adipose tissue. Neither IL-6R nor IL-8 or IL-18 showed strong relationships vs the traditional measurements. Weak relationships between IL-16 levels and trunk SAT volume was found by Imiomics. On the contrary, IL-8 levels were related to a reduction of SAT volume. Abstract: Background: Obesity has previously been linked to inflammation. Here we investigated how plasma levels of six interleukins were related to body fat distribution. Methods: In 321 subjects, all aged 50 years, in the population-based POEM study (mean BMI 26–27 kg/m 2 ), six interleukins were measured together with a DXA scan for determination of fat and lean mass. Also a whole-body magnetic resonance imaging (MRI) scan, in which fat content measurements were acquired in > 1 million voxels was performed. Interleukin levels were related to each of these voxels by the voxel-based technique "Imiomics" to create a 3D-view of how these measurements were related to size of each part of the body. Results: Levels of IL-1RA and IL-6 were related to traditional DXA and MRI measurements of adipose tissue at all locations. Neither IL-6R, nor IL-8 or IL-18, showed any consistent significant relationships vs the traditional measurements of body composition, while IL-16 showed relationships being of borderline significance. The Imiomics evaluation further strengthen the view that IL-1RA and IL-6 were related to subcutaneous adipose tissue (SAT), as well to ectopic fat distribution. In women, IL-16 levels were weakly related to expansion of SAT in the upper part of the body, while on the contrary, IL-8 levels were related to a reduction of SAT volume. Conclusion: Of the six evaluated interleukins, plasma IL-1RA and IL-6 levels were related to the amount of adipose tissue in all parts of the body, while a diverse picture was seen for other interleukins, suggesting that different interleukins are related to fat distribution in different ways.